Effectiveness of Audio-Visual Media Towards Learning Achievement Students Subjects of The History of Islamic Culture In MTs Muhammadiyah Ponorogo - Agus Budiman; Muhammad Abdu Syakur Fadlillah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
Low value indicates that students ' understanding is very low on material that has been delivered by educators. The acquisition of average value in the subjects of Islamic History of the class VII MTs Muhammadiyah 2 Jenangan is lower than the minimum submission criteria (KKM) with a score of 36.70 < 70. This is due to many factors and among these factors is no use of media in learning. Based on the purpose of studying the history of Islamic culture is to study the foundation of doctrine, values and Islamic norms, as well as the core uptake of Islamic historical events. Thus, the use of audio-visual media is deemed capable to stimulate the learning interest of students so that it can support learning achievement. This research aims to determine the differences before and after the use of audio-visual media and the effectiveness of audio-visual media in support of students ' learning achievement in the history of Islamic culture in MTs Muhammadiyah. This study was designed by experimental research with non-equivalent control group design. The population in this research is a class VII MTs Muhammadiyah 2 Jenangan amounting to 69 students, then sampling using the technique cluster sampling consists of an entire class VII which is divided into two classes, namely Class A as an experimental class with the number of 34 students and class B as the control class with the number of 35 students. Analysis of the research data uses the U-Test (Mann-Whitney). After the implementation of audio-visual media in the experimental classes and conventional methods of the control class can be found: a. The average increase in achievement of learning in the experimental class was 70.00 and the control class was 57.00, B. The hypothesis test uses the U-Test (Mann-Whitney) by indicating the value of the Sig. (2-tailed) 0.000 smaller than 0.05 and C. Hypotheses test results using test-u demonstrate that the use of audio visual media in the subjects of Islamic cultural history effective against the learning achievement of Class VII students in MTs Muhammadiyah 2 Jenangan, school year: 2019/2020.